Analysis of PV and QV Curves in Power Flows for Stability in SEP Through the Integration of Wind Power - Freire Freire, Armando Salvador (2024)
This document shows a power flow case study called "12-bar test system for wind energy integration studies" which is replicated using Power Factory Digsilent software, in order to have the power flow as close as possible to the case study. At the end of the power flow study, PV (Power-Voltage) and PQ (Active Power - Reactive Power) curve studies are carried out to analyze the stability of the SEP electrical system. The PV study evaluates the relationship between active power and voltage of the electrical power system and the PQ study evaluates the relationship between active and reactive power in the system. The studies carried out allow to identify which are the strongest and weakest bars of the system in case of n-1 contingencies, allowing to establish safe operation limits that can operate the electric power system complying with the values of active and reactive power without affecting the voltage stability in the network, as a result, the worst case scenario of the system under study is presented and the recommendations that can be implemented to counteract the problem.